Analisis Strategi Pengembangan Usaha Ayam Potong Dengan Pendekatan SWOT (Studi Kasus Pada UD. 28 Broiler Di Kota Metro) - Selamet Fuadi; Suwarto; Mida Widya Ningrum (Jurnal Manajemen DIVERSIFIKASI, 2025)
In an effort to develop a business, there are a number of tasks and steps that must be taken toachieve optimal business opportunities and maintain competitiveness in the market. Thebroiler business is one example of a promising business that has good potential in thebusiness world, this can be seen from the continuous increase in demand. The purpose of thisstudy was to determine the development strategy of broiler business by identifying relatedmatters in internal factors including strengths and weaknesses, as well as external factorsincluding opportunities and threats. This research uses qualitative methods, with datacollection techniques carried out by interviewing business owners and observation. The dataobtained was analyzed using SWOT which includes IFAS, EFAS, IE matrix and SWOT matrixmethods. The results of this study indicate that UD. 28 Broiler is in quadrant 2, where in thisquadrant it is required to carry out a diversification strategy that requires the Company tomake changes by changing or expanding the product range, in order to close weaknesses andtake advantage of existing opportunities.